2016
DOI: 10.1016/j.cels.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics Quantification of Species Variation of Escherichia coli Links Molecular Features with Strain Phenotypes

Abstract: Escherichia coli strains are widely used in academic research and biotechnology. New technologies for quantifying strain-specific differences and their underlying contributing factors promise greater understanding of how these differences significantly impact physiology, synthetic biology, metabolic engineering, and process design. Here, we quantified strain-specific differences in seven widely used strains of E. coli (BL21, C, Crooks, DH5a, K-12 MG1655, K-12 W3110, and W) using genomics, phenomics, transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 124 publications
8
137
0
Order By: Relevance
“…The K-12 strains produced approximately 0.7 mol acetate per mol glucose, in good agreement with previous reports (Chen et al, 2011; Leighty and Antoniewicz, 2013; Rahman and Shimizu, 2008). The BL21 strain produced significantly less acetate (0.39 mol/mol), a phenotype which has also been well characterized previously (Monk et al, 2016; Waegeman et al, 2012, 2011). In fact, previous studies have reported even lower acetate yields of 0.2 mol/mol and less, which may indicate a relatively larger variability in BL21 strains compared to K-12 strains.…”
Section: Resultssupporting
confidence: 80%
“…The K-12 strains produced approximately 0.7 mol acetate per mol glucose, in good agreement with previous reports (Chen et al, 2011; Leighty and Antoniewicz, 2013; Rahman and Shimizu, 2008). The BL21 strain produced significantly less acetate (0.39 mol/mol), a phenotype which has also been well characterized previously (Monk et al, 2016; Waegeman et al, 2012, 2011). In fact, previous studies have reported even lower acetate yields of 0.2 mol/mol and less, which may indicate a relatively larger variability in BL21 strains compared to K-12 strains.…”
Section: Resultssupporting
confidence: 80%
“…This is most likely due to utilization of the Phosphoenolpyruvate Carboxylase (PPC) in MG1655 and W3110 (McCloskey et al, 2016a(McCloskey et al, , 2016b, and overall increased levels of TCA cycle intermediates in strain C. E. coli MG1655 and W3110 were also found to have the highest levels of L-arginine. It should be noted that when compared to the transcript levels or flux predictions of the amino acid producing pathways (Monk et al, 2016), little correlation between the absolute metabolite concentrations was found, which indicates the difficulty in predicting metabolite levels through indirect evidence as is consistent with previous works (Daran-Lapujade et al, 2007;Hackett et al, 2016). Levels of central metabolism intermediates differed vastly between the strains (Fig.…”
Section: Rapidrip Vs Fullripsupporting
confidence: 80%
“…Hierarchical clustering (Fig. 4A) reveals that similar to gene expression levels, the levels of intracellular metabolites do not reflective genomic distances between the strains (Monk et al, 2016). The hierarchical clustering is also consistent with how the strains group by Partial Least Squares Differential Analysis (PLS-DA, Fig.…”
Section: Rapidrip Vs Fullripsupporting
confidence: 61%
See 2 more Smart Citations